Pengaruh Pemberian Pupuk Organik “Paniwang” Terhadap Produksi Dan Kandungan Nutrisi Biomassa Sorgum Lokal Sumba Umur Panen 100 Hari - Hamu, Melania Loda Ana; Sudarma, I Made Adi; Pati, Denisius Umbu (JURNAL PETERNAKAN SABANA, 2025)
The increasing livestock population triggers the need for forage feed, but limited land and land conversion are obstacles. Sorghum (Watar hammu) Kiku mbimbi, a local variety of East Sumba, has the potential as livestock feed because it is tolerant of dry land and nutritious, but its productivity is influenced by environment and fertilization. This study examines the effect of Paniwang fertilizer on the nutrition and fresh weight production of 100-day-old sorghum. Using a completely randomized design (CRD) with 5 fertilizer dose treatments (0, 10, 20, 30, 40 tons/ha) and 4 replications, the study at the Field Laboratory of Universitas Kristen Wira Wacana Sumba (March-June 2024) measured fresh material production and nutrition (proximate test), analyzed by ANOVA and DUNCAN (95% confidence). The results showed that Paniwang fertilizer significantly affected sorghum production and nutrition. The optimal dose of 30 tons/ha (P3) produced the highest fresh weight (521.20 grams), while high doses (40 tons/ha, P4) reduced production. There was variation in nutrient content between treatments: treatment without fertilizer (P0) produced the highest dry matter (DM) (87.910%) and the lowest metabolizable energy (ME) (2,808.95 kcal/kg), treatment of 10 tons/ha (P1) produced the highest crude protein (CP) (7.460%) and the lowest crude fiber (CF) (13.741%), and treatment of 20 tons/ha (P2) produced the highest ME (3,182.70 kcal/kg). This study confirms that variety, fertilization, harvest age, and environmental conditions affect sorghum nutrient content, which needs to be considered to improve sorghum-based feed quality. Paniwang fertilizer is effective in increasing sorghum production and nutrient content, serving as a reference for the development of sustainable alternative feed.